2001
DOI: 10.1016/s0009-2614(01)00430-4
|View full text |Cite
|
Sign up to set email alerts
|

New type of antiferromagnetic state in stacked nanographite

Abstract: Nanographite systems, where graphene sheets of the orders of the nanometer size are stacked, show novel magnetic properties, such as, spin-glass like behaviors and the change of ESR line widths in the course of gas adsorptions. We theoretically investigate stacking effects in the zigzag nanographite sheets by using a tight binding model with the Hubbard-like onsite interactions. We find a remarkable difference in the magnetic properties between the simple A-A and A-B type stackings. For the simple stacking, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 16 publications
3
33
0
1
Order By: Relevance
“…The magnetic moment increases as U becomes larger as expected for the increase of the localized characters of electrons. In contrast, the magnetic moment is a weak decreasing function with respect to d. shell electron system is in contrast with that of the closed shell electron system reported in the paper [7]. The present calculation is in qualitative agreement with that of the experiment which reports the decrease of the magnetization in the course of the adsorption of molecules [4,5].…”
Section: Results Of Model IIsupporting
confidence: 88%
See 2 more Smart Citations
“…The magnetic moment increases as U becomes larger as expected for the increase of the localized characters of electrons. In contrast, the magnetic moment is a weak decreasing function with respect to d. shell electron system is in contrast with that of the closed shell electron system reported in the paper [7]. The present calculation is in qualitative agreement with that of the experiment which reports the decrease of the magnetization in the course of the adsorption of molecules [4,5].…”
Section: Results Of Model IIsupporting
confidence: 88%
“…In the calculations, the finite magnetization develops, as the hopping interactions between layers increase in the case of the A-B stacking [6]. The same conclusion has been obtained when the system is near the A-B stacking and the interlayer distance becomes shorter [7]. The A-B stacking should exist in nanographite systems, because the exotic magnetisms have been observed in recent experiments [1][2][3].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The Pauli susceptibility decreases due to the decrease of the magnetic moment magnitude. We have studied the magnetism of the nanographite using the tight binding model including the interlayer interaction between neighboring nanographene layers [6][7][8]. We have found that open shell nature of each layer might explain the experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…The Hubbard model [5][6][7] is applied to π-electrons on the curved molecules. We will discuss that the molecular structure determines the magnetism in the sumanene, while the edge state gives magnetism along the zigzag edge of a part of C 60 .…”
Section: Introductionmentioning
confidence: 99%